Mollusks attached to natural mangrove roots and silvofisheries in Nabire Papua: to what extent are they different - Maitindom, Frits A; Mamangkey, Gustaf; Boneka, Farnis B. Boneka; Lasut, Markus T.; Mantiri, Rose O. S. E.; Bara, Robert. A. (Jurnal Ilmiah PLATAX, 2024)
The research aim on natural mangrove forests and silvofishery is to determine the community structure of attached invertebrates to silvofishery and natural mangrove ecosystems. I was comparing the community structure of attached invertebrates in mangrove silvofishery and natural mangrove ecosystems. Sampling was done by dredging the mangrove root skin, the collected samples were then sieved using a sieve with a mesh size of 1.0 mm using salted water and then put into sample bottles and preserved using 70% alcohol solution, then the samples were identified in the laboratory. The chemical physical parameters at both locations are within the normal range in the development of mangrove-attaching invertebrates. The two study sites contained 4 families (Potamididae, Littorinidae, and Muricidae) 7 species of which 3 species were in natural mangroves Littoraria scabra (Linnaeus, 1758), Nerita planospira (Anton, 1838), and Terebralia palustris (Linnaeus, 1767) compared to mangroves In Silvofishery there are 4 species of Chicoreus capicinus (Lamarck, 1822), Cerithidea quadrata (G. B. Sowerby II, 1866), Nerita picea (Recluz, 1841), and Cerithidea obtuse (Lamarck, 1822). The density of the mangrove-attaching anvertebtata in the mangrove forest of Sylvofishery was the highest, namely L. scabra (0.14 ind/m2 ) and the lowest was T. palustris (0.01 ind/m 2 ) Attachment invertebrate diversity at both study sites was in a low condition, and high dominance and uniformity. Keywords: Biofouling, artificial and Silvofishery, Nabire Abstrak Tujuan dari penelitian yang dilakukan pada hutan mangrove alami dan Silvofishery adalah Mengetahui struktur komunitas moluska pada ekosistem mangrove silvofishery dan mangrove alami. Membandingkan struktur komunitas moluska pada ekosistem mangrove silvofishery dan mangrove alami. Pengambilan sampel dengan mengkeruk kulit akar mangrove, sampel yang telah terkumpul kemudian dimasukan kedalam botol sampel dan diawetkan menggunakan larutan alkohol 70%, kemudian sampel diidentifikasi di Laboratorium. Parameter fisik kimia pada kedua lokasi dapat dikatakan dalam range yang normal dalam perkembangan moluska mangrove. Kedua lokasi penelitian terdapat 4 family (Potamididae, Littorinidae, dan Muricidae) 7 spesies dimana 3 spesies pada mangrove alami (Littoraria scabra (Linnaeus, 1758), Nerita planospira (Anton, 1838), dan Terebralia palustris (Linnaeus, 1767) sedangkan pada mangrove Silvofishery terdapat 4 spesies Chicoreus capicinus (Lamarck, 1822), Cerithidea quadrata (G. B. Sowerby II, 1866), Nerita picea (Recluz, 1841), dan Cerithidea obtuse (Lamarck, 1822). Kepadatan moluska mangrove pada hutan mangrove Sylvofishery tertinggi yaitu L. scabra (0,14 ind/m2 ) dan terendah yaitu T. palustris (0,01 ind/m 2 ) Keanekaragaman moluska pada kedua lokasi penelitian barada pada kondisi rendah, dan dominansi tinggi dan seragaman. Kata kunci: Moluska, Mangrove Alami dan Silvofishery, Nabire